INITIAL SEED WEIGHT AND SCARIFICATION AFFECT in vitro GERMINATION OF Echinocactus parryi (Engelm.) Gg EL PESO INICIAL DE SEMILLAS Y LA ESCARIFICACIÓN AFECTAN LA GERMINACIÓN in vitro DE Echinocactus parryi (Engelm.) - Osuna Avila, Pedro (2022)
The endemic and threatened species Echinocactus parryi, native to the municipality of Juarez, Chihuahua, Mexico, presents important limitations for its reproduction and natural propagation. It is hypothesized that initial seed weight and scarification would affect the percentage of seed germination of this species. The objective was to compare the effect of initial seed weight (two levels) and scarification treatments (four levels) on in vitro germination of E. parryi. The morphology of seedlings grown for 12 months was also described. Four hundred seeds were divided into two groups of 200 seeds each: first group, seeds of 35 to 45 mg; and second group, seeds of 46 to 55 mg. The scarification treatments were a control (intact seeds), mechanical scarification, application of 25 % sulfuric acid and Murashige and Skoog growing medium added with 2 mg L-1 of gibberellic acid. Fifty seeds per treatment were placed for each weight group. Treatments were distributed in a completely randomized experiment with factorial arrangement. Data were subjected to analysis of variance and means were compared by Tukey’s test (p ≥ 0.05). Results showed significance in the interaction of seed weight and mechanical scarification treatment by obtaining 93.2±3.6 % germination in seeds of 35 to 45 mg and 96.0±3.3 % in seeds of 46 to 55 mg at 30 d of in vitro culture. The morphological description of the seedlings provided information on the development of E. parryi in juvenile stages, which differs from the adult stage. Results on germination and the morphological description of the seedlings represent an important advance for propagation and conservation purposes. To our knowledge, this is the first report on scarification treatment in seeds of different weights and the influence on germination, that also recorded the seedling morphology of E. parryi.